1993
DOI: 10.1001/archsurg.1993.01420180035007
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Hormone Receptors, Cathepsin D, and HER-2/neu Oncoprotein in Normal Colon and Colonic Disease

Abstract: Further analyses are needed to determine which parameters are related to and possibly predictive of increased carcinoma risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 18 publications
3
17
0
1
Order By: Relevance
“…3,11 It also has mitogenicproperties 12 and facilitates the releaseof angiogenic factor and basic fibroblast growth factor, stimulating neovascularization. 13 Galanduiket al, 14 using immunoassay, showed increased CD levels in neoplastic colon tissues with respect to the normal colon, regardless of whether cells expressed this protease. Theodoropouloset al, 1 performing immunohistochemistry with a monoclonal antibody, detected CD in tumor and stromal cells in colon cancer specimens.…”
Section: Discussionmentioning
confidence: 97%
“…3,11 It also has mitogenicproperties 12 and facilitates the releaseof angiogenic factor and basic fibroblast growth factor, stimulating neovascularization. 13 Galanduiket al, 14 using immunoassay, showed increased CD levels in neoplastic colon tissues with respect to the normal colon, regardless of whether cells expressed this protease. Theodoropouloset al, 1 performing immunohistochemistry with a monoclonal antibody, detected CD in tumor and stromal cells in colon cancer specimens.…”
Section: Discussionmentioning
confidence: 97%
“…The results of recent publications on colonic mucosal EGFR activity in IBD bring discrepant conclusions. Galandiuk and Trzcinski observed high expression of EGFR in colonic mucosa in a murine model of colitis, which according to the authors suggested a role of this receptor in promoting the inflammatory response [6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…High expression of ErbB mucosal receptors (EGFR family member) was shown in active phases of inflammatory diseases -IBD [6][7][8][9], asthma [10], rheumatoid arthritis [11]. On the other hand, other authors suggest that EGFR inhibition might cause NFκB activation, resulting in an inflammatory response [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Cathepsin D has also been found at a high lcvcl in colon cancer (Galandiuk et al, 1993). We have previously reportcd that the HT-29 colon carcinoma cell line secretes pro-cathepsin D in its culture medium (Huet et al, 1994), suggesting that this proteinase might be also involved in the neoplastic progression of colon cancers.…”
mentioning
confidence: 93%